2014
DOI: 10.1111/ger.12129
|View full text |Cite
|
Sign up to set email alerts
|

Sedative load and salivary secretion and xerostomia in community‐dwelling older people

Abstract: Sedative load is strongly related to hyposalivation and to a lesser extent with xerostomia. The adverse effects of drugs on saliva secretion are specifically related to drugs with sedative properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
1
7
1
Order By: Relevance
“…This seemingly unexpected observation supports the earlier-mentioned explanation that it is a question of qualitative changes in microbiota in the oral cavity, most likely related to low salivary secretion, which seem to create favourable conditions for cariogenic bacteria but not for periodontal pathogens [37][38][39] . The fact that sedative load was more or less inversely associated with periodontal pocketing is in accordance with previous results from the GeMS study showing that sedative load was associated with low salivary flow 21 and that low salivary secretion was inversely associated with periodontal pocketing 40 . Although this explanation seems to be the most probable, there are other explanations as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This seemingly unexpected observation supports the earlier-mentioned explanation that it is a question of qualitative changes in microbiota in the oral cavity, most likely related to low salivary secretion, which seem to create favourable conditions for cariogenic bacteria but not for periodontal pathogens [37][38][39] . The fact that sedative load was more or less inversely associated with periodontal pocketing is in accordance with previous results from the GeMS study showing that sedative load was associated with low salivary flow 21 and that low salivary secretion was inversely associated with periodontal pocketing 40 . Although this explanation seems to be the most probable, there are other explanations as well.…”
Section: Discussionsupporting
confidence: 91%
“…The study protocol was approved by the ethics committee of Kuopio University Hospital and the University of Kuopio. More information about the GeMS study can be found in the papers by Lampela et al 18 and Tikkanen et al 19 and about the Oral Health GeMS study in the papers by Komulainen et al 20 and Tiisanoja et al 21…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that simultaneous use of multiple drugs, regardless of class or type, can have an additive effect to cause dry mouth, especially xerostomia. [30][31][32][33] In contrast, our previous study from the same GeMS population 34 showed that the number of drugs by itself is not an essential risk factor for hyposalivation, but the effects of the drugs are carried out by drugs with sedative properties. The present study also lends support to the assumption that the total number of drugs itself might not be a major risk factor for hyposalivation or xerostomia.…”
Section: Discussionmentioning
confidence: 66%
“…These findings are in line with our previous study, which showed similar results regarding the effects of drugs with sedative properties and the total number of drugs. 34 Because the adjustments for the total number of drugs, antihypertensives or sedative drugs caused only a slight attenuation of the relative risks, the effect of anticholinergic burden appears to be independent of the above-mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, salivary glands are very vulnerable to certain exogenous factors, such as side effects of medications with sedative or anticholinergic properties . A previously published paper of NutOrMed baseline data of 270 home care clients reported that excessive polypharmacy, use of particular drug groups and depression symptoms were associated with xerostomia.…”
Section: Discussionmentioning
confidence: 99%